Solubility, structure transition and chemical durability of Th-doped Nd2Zr2O7 pyrochlore. (July 2021) - Wang, Lielin; Li, Jiangbo; Xie, Hua; Chen, Qingyun; Xie, Yuqi
Abstract: Pyrochlore is regarded as a potential host matrix for actinides of high-level radioactive wastes. Thorium-doped neodymium zirconate pyrochlore samples were prepared by spray-pyrolysis method and characterized by XRD，SEM-EDS and Raman spectroscopy. The solubility limit of Th in Nd2-x Thx Zr2 O7+ δ (x = 0.0–2.0) pyrochlore was estimated up to be 20 at%. The multi-phase ceramic structure composed of pyrochlore, fluorite thoria and tetragonal zirconia was observed at x > 0.4. Rietveld refinement and Raman analysis of Nd2-x Thx Zr2 O7+ δ （x = 0.0–0.3）samples showed the single pyrochlore structures, the lattice parameter decreases with Th content increasing. The lattice parameter and O48 f positional parameter of the Nd1.6 Th0.4 Zr2 O7 sample have increased significantly，indicating that the crystal structure undergoes a phase transition from ordered pyrochlore to disordered pyrochlore due to the distorted B O6 octahedron. The Nd2-x Thx Zr2 O7+ δ (x = 0.0–0.4) pyrochlore samples exhibit low leaching rate. From these results, the high solubility of actinides, structure stability and chemical durability are reflected in the Th-doped Nd2 Zr2 O7 pyrochlore samples. The present work provides a potential synthetic method and nuclear waste forms for the immobilization of high-level radioactive waste in the nuclear industry. Highlights: Up to 20 at% of thorium in Nd2 Zr2 O7 pyrochlore was prepared. The structures of Nd2-x Thx Zr2 O7+ δ pyrochlores were investigated. Th-doped Nd2-x Thx Zr2 O7+ δ pyrochlores exhibit high chemical durability. A novel practical aqueous synthesis route and nuclear waste form were proposed for immobilization of high-level wastes.